The Effect of Fundamental Factors and Earnings Growth on Stock Prices in Food and Beverage Subsector Companies on the IDX for the 2019-2023 Period - Ima Andriyani; Triana, Asti; Marzuki, Agustina (CV Putra Publisher, 2024)
This study aims to determine and analyze the effect of Fundamental Factors consisting of Earning Per Share (EPS), Price to Book Value (PBV), Price to Earning Ratio (PER) and Earnings Growth on Share Prices in food and beverage subsector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample used in this study is the financial statements of food and beverage subsector companies for the period 2019 to 2023. The method used in determining the sample is by using purposive sampling method, and obtained as many as 13 companies. Data analysis used in research with the Eviews program. The results showed that EPS has a significant effect on stock prices, PBV has a significant effect on stock prices, PER has a significant effect on stock prices, earnings growth has no significant effect on stock prices. While simultaneously EPS, PBV, PER and earnings growth have a significant effect on stock prices. The implication in this study is that the signaling theory of the research results affects the rise and fall of stock prices. In view of the high fundamental factors, it shows a positive signal for the company, especially in stock prices. However, it does not apply to earnings growth because if earnings growth is high, it will have a bad effect on stock prices as well as for investors, but investors can look deeper into financial ratios.